2016
DOI: 10.1159/000446713
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Colorectal Cancer

Abstract: It is known that the immune response, reflected by high T cell infiltrates in primary tumors and metastases, influences the clinical course of colorectal cancer (CRC). Therefore, immunotherapy concepts have been adapted from other tumor entities, which typically rely on the activation of T cells in the tumor microenvironment (e.g. blockade of the immune checkpoint molecules PD-1 and CTLA-4). However, most of the strategies using the approved checkpoint inhibitors and/or combination strategies have more or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The current approaches to treat metastatic CRC (mCRC) involve multimodal therapy based on chemotherapy (including the combination of cytotoxic drugs) or targeted agents (such as bevacizumab, cetuximab, and panitumumab) (114). In the last few years, immunotherapy, which typically rely on the activation of T cells in the TME, has been considered for mCRC patients (115). Checkpoint inhibitors such as antibodies directed against cytotoxic T lymphocyte antigen-4 (CTLA-4) and programmed cell death protein (PD-1)/PD-1 ligand (PD-L1) resulted ineffective to produce durable clinical responses due to tumor-mediated immune evasion and resistance, caused by the presence, into the TME, of immunosuppressive cells like MDSCs (116).…”
Section: Mdscs In Colorectal Cancermentioning
confidence: 99%
“…The current approaches to treat metastatic CRC (mCRC) involve multimodal therapy based on chemotherapy (including the combination of cytotoxic drugs) or targeted agents (such as bevacizumab, cetuximab, and panitumumab) (114). In the last few years, immunotherapy, which typically rely on the activation of T cells in the TME, has been considered for mCRC patients (115). Checkpoint inhibitors such as antibodies directed against cytotoxic T lymphocyte antigen-4 (CTLA-4) and programmed cell death protein (PD-1)/PD-1 ligand (PD-L1) resulted ineffective to produce durable clinical responses due to tumor-mediated immune evasion and resistance, caused by the presence, into the TME, of immunosuppressive cells like MDSCs (116).…”
Section: Mdscs In Colorectal Cancermentioning
confidence: 99%
“…Also, immunotherapy quickly reached clinical application in melanoma, 2 while gastrointestinal cancer types are still lagging behind. 3 These shifts within the cancer immunotherapy field are highly relevant for clinicians, researchers and funding agencies. However, until now, these changes have not been quantified in a way that allows an unbiased assessment of past and possible future trends.…”
Section: Introductionmentioning
confidence: 99%
“…These results support a genetically-guided approach to immunotherapy in this unique subset. Currently, checkpoint inhibitors approved for different indications as well as novel checkpoint inhibitors (TIM-3, Lag-3, OX40, GITR, 4-1BB, CD40, CD70) are being studied in CRC (91). Recent work showed that MEK inhibition promotes infiltration of effector CD8 + T cells and synergize with a PD-L1 inhibitor in preclinical models (92).…”
Section: Crcmentioning
confidence: 99%